Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„ØªÙ‚Ø§Ø¨Ù„ÙŠØ© Ø¨ÙŠÙ† Ø§Ù„Ø£ØµÙˆØ§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ùˆ Ø§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ© Ùˆ ØªØ·Ø¨ÙŠÙ‚Ù‡Ø§ ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø®Ø¯Ù… Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨Ø© - Zubaidi, Ahmad; Dewi, Rosiana Anggraini (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2019)
this study aimed to describe the comparison of phonology of Arabic and Indonesian and to reveal the location of the similarities and differences between the both of it. This study uses a descriptive qualitative approach. The findings of this study are: 1) the sound of Arabic is six types, three short and three long. The short sound type is (Ù€ÙŽ ØŒ Ù€Ù ØŒ Ù€Ù), and the long sound is Ø§ ØŒ Ùˆ ØŒ ÙŠ. While the sound of Indonesian is seven, and all of it is short, namely, a, i, u, e, o. Long sounds do not exist in Indonesian, so students do not have difficulty distinguishing. 2) Arabic has 22 silent sounds, that is, Ø¨ ØŒ Øª ØŒ Ø« ØŒ Ø¬ ØŒ Ø Ø® Ø® ØŒ Ø¯ ØŒ Ø° ØŒ Ø± ØŒ Ø² ØŒ Ø³ ØŒ Ø´ Øµ Øµ ØŒ Ø¶ ØŒ Ø· ØŒ Ø¸ ØŒ Ø¹ ØŒ Øº ØŒ Ù ØŒ Ù‚ ØŒ Ùƒ ØŒ Ù„ ØŒ Ù… ØŒ Ù† ØŒ Ùˆ ØŒ Ù‡ ØŒ Ø¡ ØŒ ÙŠ ØŒ. While Indonesian has 20 mute sounds, namely b, c, d, g, h, j, k, l, m, n, ny, ng, p, r, s, t, w, y. 3) the sound of Arabic that has no equivalent in Indonesian, including Ø« ØŒ Ø ØŒ Ø® ØŒ Ø° ØŒ Ø² ØŒ Ø´ ØŒ Øµ ØŒ Ø¶ ØŒ Ø· ØŒ Ø¸ ØŒ Ø¹ ØŒ Øº ØŒ Ùˆ. Therefore, to minimize the difficulties of students, these differences need to be taught gradually, starting from the easy to the difficult. The methods that can be used include: the Abjadiyah method, the sound method and the language dualism method